Analisis Kinerja Anggaran Pendapatan Dan Belanja Daerah Pada Pemerintah Daerah Kabupaten Oku Periode 2013-2017 - Hasiatul Aini; Mardiah Kenamon; Yeni Anggraini (Universitas Bandar Lampung (UBL), 2020)
Data used is secondary data. The analysis models used in this study are the ratio of the degree of decentralization, the ratio of regional financial dependency, the ratio of effectiveness and efficiency of Own-Source Revenue, ratio of expenditure efficiency, ratio of regional expenditure to GRDP. The results find that the ratio of the degree of decentralization is Very Less, the ratio of regional financial dependence is Very High, Own-Source Revenue is Effective, ratio of Own-Source Revenue is efficient and the ratio of expenditure efficiency is quite Efficient. The analysis of Own-Source Revenue in the District Government of Ogan Komering Ulu in the period of 2013-2017 is effective, while regional expenditure is efficient.